Orange-fleshed sweetpotato is a critical component of the Kenya Accelerated Value Chain Development (AVCD) Program - International Potato Center (2017)
At the end its second year, 47 decentralized vine multipliers are operational and a total of 36,313 households have been reached with structured nutrition education that integrates essential messages for Maternal and Infant and Young Child Nutrition. Progress has been made in initiating fresh root and processed product value chains.